ASC360: Personal Financial Planning / College of Computing, Informatics and Mathematics - UiTM, College of Computing, Informatics and Mathematics (2023)
This course introduces the students to the personal financial planning. The syllabus for this course provide with the basic understanding of financial planning concept.